Patient satisfaction constructs - Rahman, Muhammad Sabbir; Osman-Gani, Aahad M. (Emerald Management Review, 2015)
Purpose – The purpose of this paper is to examine the five-factor structure of patients’ satisfaction constructs toward private healthcare service providers. Design/methodology/approach – This research is a cross-sectional study. A questionnaire-based survey was conducted with previous and current Bangladeshi patients. Exploratory factor analysis was employed to extract the underlying constructs. Findings – Five underlying dimensions that play a significant role in structuring the satisfaction perceived by Bangladeshi private healthcare patients are identified in this study. Practical implications – The main contribution of this study is identifying the dimensions of satisfaction perceived by Bangladeshi patients regarding private healthcare service providers. Originality/value – Healthcare managers adopt the five identified underlying construct items in their business practices to improve their respective healthcare efficiency while ensuring overall customer satisfaction. Keywords Costs, Corporate image, Functional quality, Technical quality,External uncontrollable influence, Internal controllable influence Paper type Research paper